Between the denial of realities and pragmatism: migration-led regeneration in Genova and Manchester - Hillmann, Felicitas (Raumforschung und Raumordnung | Spatial Research and Planning, 2019)
Starting from the assumption that urban politics are a fundamental part of an evolving local governance of migration, this article investigates the overlappings between migration-related policies and migrant agency on one hand and urban regeneration policies on the other hand. As European cities are embedded in (supra-)national migration regimes, the institutional responses on migration vary accordingly. The here presented comparison between two cities in two migration regimes allows for an understanding of common traits and differences of the urban governance of migration across the different migration regimes. For this purpose the situation in Genova (Italy) and Manchester (UK) is in the focus of the analysis. The comparison reveals that as well cities with long-established migration policies as those with a poorly developed institutional setting strongly rely on the agency of the civil society. Migration-led regeneration takes place, but is not framed explicitly within the urban policies and strategies of regeneration.
Keywords: Migration; Urban Regeneration; Integration; Multiculturalism; Genova; Manchester; Planning